Olympic Education as an Important Component of a Comprehensive Curriculum on Physical Culture - Vira Tkachuk; Iryna Turchyk; Roman Chopyk; Larysa Kozibroda; Maria Chemerys (Lesya Ukrainka Volyn National University, 2018)
Topicality. The Olympic education of youth is one of the most important components in the formation of a harmoniously developed personality, the development of feelings and attitudes, habits of behavior, based on the Olympic principles, the Olympic values and the Olympic ideal. Task.  To study the content component of the Olympic themes in the comprehensive curriculum on physical culture. Methods. Analysis of literary sources, method of comparative analysis, methods of theoretical interpretation. Results. The results of our research have made it possible to find out the importance and necessity of studying the Olympic theme information by schoolchildren. Conclusions. Olympic education plays an important role in the process of teaching physical education. Students engaged in sports must learn to constantly strive for self-improvement, to work daily on the development of their spiritual, mental, volitional and physical abilities.